A Systematic Review of Patient-Reported Outcomes for Surgically Amenable Epiphora. Issue 3 (May 2018) - Schulz, Christopher B.; Kennedy, Alasdair; Rogers, Simon
Abstract : Purpose: In evaluating epiphora and its management, the bottom line for all stakeholders is whether an intervention confers any real benefit on quality of life. A review was conducted to identify and appraise patient-reported outcome measures (PROMs) in surgically amenable epiphora. Methods: A systematic search was conducted of studies relating to surgical intervention for epiphora. Patient-reported outcome measures were identified and assessed against standard criteria. Results: Of 30, 544 identified articles, 227 were eligible for data extraction. Of these, 69% reported a PROM as the primary outcome. PROMs identified included single-item symptom scores (48% of primary outcome PROMs), single-item reports of improvement (30%), the Glasgow Benefit Inventory (3%), Lacrimal Symptom Questionnaire (0.5%), Nasolacrimal Duct Obstruction Symptom Score (0.5%), Ocular Surface Disease Index (0.5%), Visual Function Questionnaire-25, the Short Form-36 Health Survey, and 3 other symptom scores. None were developed through consultation with the target population, and there was inadequate testing of content validity. The strengths and limitations of each PROM are presented, with regard to interpretation, responsiveness, reliability, and validity. Discussion: The importance of robust and psychometrically sound PROMs is essential if the under-reporting of quality of life improvement in patients treated for epiphora is to change. Recommendations for the use of each identified PROM are discussed. Conclusions: Several PROMs have been used in the recent literature to evaluate patients undergoing surgery to treat epiphora. Assessed against standard criteria, no PROM has proven to be both psychometrically robust and clinically meaningful for use in this population. Future PROM development should be guided by this standard framework. Abstract : Over 97% of epiphora research includes patient-reported outcome measures (PROMs), yet when evaluated against set criteria, no PROM has proven to be both psychometrically robust and clinically meaningful in this population.Supplemental Digital Content is available in the text.